Fuzje i przejęcia w gospodarce światowej w 2005 r. - Adamczyk, Marzena; Piasecka-Głuszak, Agnieszka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
Processes taking place in the world economy, increasing globalization, competition on international markets, countries changing their economic policy, liberalization of economies, easy and fast flow of capital - these are just some of the factors that indicate the reason for choosing M&A as one of the possible forms of internationalization. This article's objective is to present ideas related to mergers of the companies, mergers and acquisitions (M&A) in the world economy in 2005, processes in particular, characteristic features of M&A worth over 1 million $ in 2005, as well as to present the biggest M&A. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 11-20